2019
DOI: 10.1007/s00429-019-01894-w
|View full text |Cite
|
Sign up to set email alerts
|

Relations between cognitive and motor deficits and regional brain volumes in individuals with alcoholism

Abstract: Despite the common co-occurrence of cognitive impairment and brain structural deficits in alcoholism, demonstration of relations between regional gray matter volumes and cognitive and motor processes have been relatively elusive. In pursuit of identifying brain structural substrates of impairment in alcoholism, we assessed executive functions (EF), episodic memory (MEM), and static postural balance (BAL) and measured regional brain gray matter volumes of cortical, subcortical, and cerebellar structures commonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 60 publications
(57 reference statements)
0
14
0
1
Order By: Relevance
“…Regression analysis revealed that the rostral middle frontal and cerebellar cortical volume were significant selective predictors of performance on an executive functions battery and critically not of a test of general cognitive status (Nakamura-Palacios et al, 2014). Relative to controls, alcoholics scored lower on three sets of composite scores and had smaller frontal, cingulate, insular, parietal, and hippocampal volumes; within the alcoholics, executive function scores correlated with frontal and temporal volumes; explicit memory scores correlated with frontal volume; and balance scores correlated with frontal, caudate, and pontine volumes (Fama, Le Berre, Sassoon, et al, in press). A visuospatial processing deficit in long-term abstinent alcoholics was related selectively to parietal volume shrinkage but not to other cortical volume deficits; greater parietal volume shrinkage occurred with greater amount of alcohol consumed over a lifetime (Fein, Shimotsu, Chu, & Barakos, 2009).…”
Section: Neural Mechanisms Of Cognitive and Motor Correlates: Evidenc...mentioning
confidence: 99%
“…Regression analysis revealed that the rostral middle frontal and cerebellar cortical volume were significant selective predictors of performance on an executive functions battery and critically not of a test of general cognitive status (Nakamura-Palacios et al, 2014). Relative to controls, alcoholics scored lower on three sets of composite scores and had smaller frontal, cingulate, insular, parietal, and hippocampal volumes; within the alcoholics, executive function scores correlated with frontal and temporal volumes; explicit memory scores correlated with frontal volume; and balance scores correlated with frontal, caudate, and pontine volumes (Fama, Le Berre, Sassoon, et al, in press). A visuospatial processing deficit in long-term abstinent alcoholics was related selectively to parietal volume shrinkage but not to other cortical volume deficits; greater parietal volume shrinkage occurred with greater amount of alcohol consumed over a lifetime (Fein, Shimotsu, Chu, & Barakos, 2009).…”
Section: Neural Mechanisms Of Cognitive and Motor Correlates: Evidenc...mentioning
confidence: 99%
“…In AUD, neuronal loss increases with duration of alcohol abuse and is found in regions such as the orbitofrontal cortex (OFC) [ 31 , 32 , 33 ], entorhinal cortex (ENT) [ 19 , 34 ], superior frontal gyrus [ 35 ], and hippocampus [ 36 , 37 , 38 ]. Neuronal loss in the OFC is associated with cognitive impairment to promote increased risk of relapse [ 33 , 39 ], poor decision making [ 32 ], memory deficits [ 36 ], and loss of cognitive control [ 40 , 41 ]. Damage to the ENT involves learning and memory deficits through its regulation of hippocampal function [ 18 , 19 , 38 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that alcohol use disorder (AUD), characterized by chronic and excessive alcohol consumption, is associated with brain damage and cognitive deficits (Epstein, Pisani, & Fawcett, 1977;Fama et al, 2019;Oscar-Berman, Shagrin, Evert, & Epstein, 1997;Parsons, 1977;Pitel et al, 2011). Indeed, executive functions and episodic memory abilities were repeatedly reported as impaired in recently detoxified AUD patients (Le Berre, Fama, & Sullivan, 2017;Oscar-Berman et al, 2014 for a review).…”
Section: Introductionmentioning
confidence: 99%